Digital occupants – Wie digitale Medien die kommunikative Aushandlung von Freundschaften verändern - Teichert, Jeannine

Mediale Identitätsaushandlungen deutscher MigrantInnen im Zuge des Brexit - Teichert, Jeannine; Meister, Dorothee M. (MedienPädagogik)

Wie digitale Medien die kommunikative Aushandlung von Freundschaften verändern - Teichert, Jeannine

Mediale Identitätsaushandlungen deutscher MigrantInnen im Zuge des Brexit - Teichert, Jeannine; Meister., D.M. (MedienPädagogik)

Screencasting: Documenting Processuality - Eckel, Julia (Screen-Images. Screenshot, Screencast, In-Game Photography)

The Virus Is Present, Presence Is Virulent: Being Co(m)present With Others in Times of Corona - Eckel, Julia; Linseisen, Elisa (Epidemics and Othering. The Biopolitics of COVID-19 in Historical and Cultural Perspectives)

Identifizierung quantifizierbarer Bewertungsinhalte und -kategorien mittels Text Mining - Kersting, Joschka
Reading between the lines has so far been reserved for humans. The present dissertation addresses this research gap using machine learning methods. Implicit expressions are not comprehensible by computers and cannot be localized in the text. However, many texts arise on interpersonal topics that, unlike commercial evaluation texts, often imply information only by means of longer phrases. Examples are the kindness and the attentiveness of a doctor, which are only paraphrased (“he didn’t even look me in the eye”). The analysis of such data, especially the identification and localization of implicit statements, is a research gap (1). This work uses so-called Aspect-based Sentiment Analysis as a method for this purpose. It remains open how the aspect categories to be extracted can be discovered and thematically delineated based on the data (2). Furthermore, it is not yet explored how a collection of tools should look like, with which implicit phrases can be identified and thus made explicit (3). Last, it is an open question how to correlate the identified phrases from the text data with other data, including the investigation of the relationship between quantitative scores (e.g., school grades) and the thematically related text (4). Based on these research gaps, the research question is posed as follows: Using text mining methods, how can implicit rating content be properly interpreted and thus made explicit before it is automatically categorized and quantified? The uniqueness of this dissertation is based on the automated recognition of implicit linguistic statements alongside explicit statements. These are identified in unstructured text data so that features expressed only in the text can later be compared across data sources, even though they were not included in rating categories such as stars or school grades. German-language physician ratings from websites in three countries serve as the sample domain. The solution approach consists of data creation, a pipeline for text processing and analyses based on this. In the data creation, aspect classes are identified and delineated across platforms and marked in text data. This results in six datasets with over 70,000 annotated sentences and detailed guidelines. The models that were created based on the training data extract and categorize the aspects. In addition, the sentiment polarity and the evaluation weight, i. e., the importance of each phrase, are determined. The models, which are combined in a pipeline, are used in a prototype in the form of a web application. The analyses built on the pipeline quantify the rating contents by linking the obtained information with further data, thus allowing new insights. As a result, a toolbox is provided to identify quantifiable rating content and categories using text mining for a sample domain. This is used to evaluate the approach, which in principle can also be adapted to any other domain.

Towards Comparable Ratings: Quantifying Evaluative Phrases in Physician Reviews - Kersting, Joschka; Geierhos, Michaela (Data Management Technologies and Applications)
We present a concept for quantifying evaluative phrases to later compare rating texts numerically instead of just relying on stars or grades. We achievethis by combining deep learning models in an aspect-based sentiment analysis pipeline along with sentiment weighting, polarity, and correlation analyses that combine deep learning results with metadata. The results provide new insights for the medical field. Our application domain, physician reviews, shows that there are millions of review texts on the Internet that cannot yet be comprehensively analyzed because previous studies have focused on explicit aspects from other domains (e.g., products). We identify, extract, and classify implicit and explicit aspect phrases equally from German-language review texts. To do so, we annotated aspect phrases representing reviews on numerous aspects of a physician, medical practice, or practice staff. We apply the best performing transformer model, XLM-RoBERTa, to a large physician review dataset and correlate the results with existing metadata. As a result, we can show different correlations between the sentiment polarity of certain aspect classes (e.g., friendliness, practice equipment) and physicians’ professions (e.g., surgeon, ophthalmologist). As a result, we have individual numerical scores that contain a variety of information based on deep learning algorithms that extract textual (evaluative) information and metadata from the Web.

Digital Democracy and the Digital Public Sphere - Fuchs, Christian

Zur Kritik der Politischen Ökonomie des Digitalen Kapitalismus: Die Aktualität von Manfred Knoches Beitrag zur Kritik der Politischen Ökonomie der Medien und der Kommunikation - Fuchs, Christian (Eigentum, Medien, Öffentlichkeit: Verhandlungen des Netzwerks Kritische Kommunikationswissenschaft)

The Problems of Base/Superstructure and Ideology in the Works of Stuart Hall, Georg Lukács, and Raymond Williams - Fuchs, Christian (The Communication Review.)
We live in times of deep crisis. General crises of society often are accompanied by ideological struggles. Given this context, it is important that social theory reinvigorates the analysis of ideology. For doing so, it makes sense to engage with classical theories of ideology. This paper contributes to this task. It asks: How are the economic and the non-economic related? What is ideology? This article deals with the base/superstructure problem and the problem of ideology via an engagement with selected aspects of Stuart Hall’s, Georg Lukács’s and Raymond Williams’s works. The commonality of Hall’s, Lukács’s and Williams’s thoughts that makes a joint engagement with their works feasible is that they all three dealt with aspects of culture from a critical theory perspective and are in one way or another representatives of Cultural Marxism. While Lukács’s works and Cultural Studies are often presented as conflicting approaches, this paper shows that concerning the question of how the economic and the non-economic are related and how we can think of ideology, the approaches of Lukács, Williams, and Hall complement each other, which allows critical theories of culture to draw on all three approaches and to combine elements from them in a synergistic manner. There are parallels between Williams’, Hall’s, and Lukács’s solutions to the base/superstructure problem. Williams argues that the economic exerts pressures on and sets limits to the non-economic. Hall writes that the economic determines the non-economic in the first instance. Lukács argues that the economic circumscribes subjectivity and the non-economic.
Keywords: base and superstructure; culture; economy and culture; Georg Lukács; ideology; Raymond Williams; Stuart Hall

Digitale Desökonomie: Unproduktivität, Trägheit und Exzess im digitalen Milieu - Althoff, Sebastian

Food - Media - Senses

Ibn Khaldûn and the Political Economy of Communication: A Reply to Graham Murdock - Fuchs, Christian (Critical Sociology)

Medienästhetik und dann? - Bartz, Christina (Medienkritik und Wirkungsästhetik. Konvergenzen und Zuschreibungen schädlicher und wünschenswerter Rezeptionseffekte von Literatur und Medien seit dem 18. Jahrhundert)

Ibn Khaldûn and the Political Economy of Communication in the Age of Digital Capitalism - Fuchs, Christian (Critical Sociology)

Anmerkungen zum Begriff des digitalen Kapitalismus. - Christian, Fuchs (Theorien des digitalen Kapitalismus)

Technology and Civic Virtue - Reijers, Wessel (Philosophy & Technology)
Abstract Today, a major technological trend is the increasing focus on the person: technical systems personalize, customize, and tailor to the person in both beneficial and troubling ways. This trend has moved beyond the realm of commerce and has become a matter of public governance, where systems for citizen risk scoring, predictive policing, and social credit scores proliferate. What these systems have in common is that they may target the person and her ethical and political dispositions, her virtues. Virtue ethics is the most appropriate approach for evaluating the impacts of these new systems, which has translated in a revival of talk about virtue in technology ethics. Yet, the focus on individual dispositions has rightly been criticized for lacking a concern with the political collective and institutional structures. This paper advocates a new direction of research into civic virtue, which is situated in between personal dispositions and structures of governance. First, it surveys the discourse on virtue ethics of technology, emphasizing its neglect of the political dimension of impacts of emerging technologies. Second, it presents a pluralist conception of civic virtue that enables us to scrutinize the impact of technology on civic virtue on three different levels of reciprocal reputation building, the cultivation of internal goods, and excellence in the public sphere. Third, it illustrates the benefits of this conceptions by discussing some paradigmatic examples of emerging technologies that aim to cultivate civic virtue.
Keywords: History and Philosophy of Science; Philosophy

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

Agentenbasierte Modellierung und Simulation im Pandemiemanagement - Hälterlein, Jens (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Mathematical models and computer simulations play a crucial role in the context of the COVID-19 crisis for knowledge about the possible course of the pandemic and for appropriate policy decisions. The paper presents results from an ethnographic study of a government-funded R & D project dealing with agent-based modeling and simulation (ABMS) in the context of pandemic management. Based on the assumption that the use of computer simulations in pandemic management is not only a means to an end for political or epidemiological goals but also plays a significant role in determining which goals and strategies appear politically legitimate, the paper reconstructs how insights into the pandemic are generated in ABMS and specifically in the researched project and made accessible for decision-making.
Keywords: General Medicine